Effect of testosterone on the mRNA expression of Wnt-2 and dickkopf1 (DKK1), collagen deposition and oxidative stress in the cardiac tissue in male rats : Effect of testosterone on the mRNA expression - Ghowsi, Mahnaz; Sisakhtnezhad , Sajjad; Wang, Youwei (Cellular and Molecular Biology, 2023)
Some studies suggest that misuse of androgenic-anabolic steroids may increase the risk of cardiovascular diseases in males. This study explored the effects of testosterone enanthate (TE) on the total antioxidant capacity (TAC) and malondialdehyde (MDA) levels as biomarkers of oxidative stress in the cardiac tissue of rats that were treated with TE. Also, we evaluated the levels of collagen deposition as a marker for cardiac fibrosis and the mRNA expression of the Wnt-2 and dickkopf1 (DKK1) as potential factors that may be involved in the increase of collagen deposition. In this study, 21 male Wistar rats were divided into three groups (n=7): CO: controls; T-T: normal rats that were treated with 25 mg/kg/day TE for 2 weeks and served as an androgen abuse model; V-T: these animals were treated with the sesame oil as a solvent of TE. At the end of treatment, the relative mRNA expression of Wnt-2 and DKK1 in the ventricular tissue was determined by q-RT-PCR. The degree of collagen deposition in the myocardial tissue was evaluated by Masson’s trichrome staining. Results showed that the mRNA expression of DKK1 was down-regulated following excess androgen exposure (p=0.009) but Wnt-2 mRNA expression wasn’t affected (p=0.069). Increased collagen deposition was observed in the T-T group (p=0.000). The levels of MDA and TAC in heart tissue weren’t altered significantly (p>0.05). These results suggest that the raised collagen deposition by exogenous testosterone may be mediated, at least in part, by the reduction of expression of DKK1 mRNA. These findings may explain some structural alterations in the heart of some androgens abusers.